Iowa RBA, January 13-15, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for January 13-15, 1997. Highlights of the update include the continued presence of a Pinyon Jay, the return of a Varied Thrush, and an Evening Grosbeak. Other interesting observations were of nine Red Crossbills, two Snowy Owls, and a Northern Goshawk. Also included are handwritten notes for the next week's update with sightings of a Northern Saw-whet Owl and a Red-shouldered Hawk. Epson - sheet feed/flatbed